New Radio Concept for Far Field Communication - Undiano Ustarroz,Mikel (2024)
This thesis explores the state-of-the-art methods for the optimization of Wireless Power Transfer (WPT) for Radio Frequency (RF) energy harvesting with a view of increasing the efficiency of the Radio Frequency to Direct Current (RF-to-DC) conversion, which is a key parameter in the creation of Zero Energy Devices (ZEDs) in the context of Internet of Things (IoT). The research focuses on waveform shaping at the transmitter side as a technique of enhancing energy delivered to rectifiers. To achieve this, the project proposes to define arbitrary waveforms with high Peak-to-Average Power Ratio (PAPR) so as to direct more energy to the peaks of the waveform in order to enhance the rectification efficiency. The study proposes multisine signals as a reference signal and these signals have higher PAPR compared to other signals. These signals are then processed by windowing techniques like Gabor pulses and raised cosine windows thereby increasing PAPR and in turn enhancing the efficiency of the RF-to-DC conversion. The work uses theoretical modeling, simulation, and experimental testing to show that the proposed waveform shaping strategies enhance rectifier performance. It has been proved that these waveform shaping pulses that can be applied to Far Field Communication (FFC) concerns enhance the rectified DC power in order to feed any type of passive device. For the purpose of practical relevance, the thesis also provides the design and setup of a realistic test environment to evaluate the proposed ideas in a realistic setting. The experimental results also prove the efficiency of these techniques in improving the RF-to-DC conversion efficiency and the potential of energy harvesting technologies.
Keywords: RF Energy Harvesting; Wireless Power Transfer; RF-to-DC; Waveform Shaping; PAPR; Rectenna